(untitled) (Journal of The Colloquium for Information Systems Security Education, 2017)
The purpose of this paper is to create public awareness for privacy and to better protect consumers from Smart TV vulnerabilities. The analysis highlights many of the seemingly harmless Samsung preloaded applications that offer consumers little privacy. With the skyrocketing sales of Smart TVs, comes a critical challenge to protect customers’ Personally Identifiable Information (PII). The need to educate and drive security awareness falls on both the private and public sector.Manufacturers, retailers, customers, and legislators need to help define the scope of protection required to mitigate the risk. This paper looks at the need to create public awareness for privacy and explore possible mitigation strategies to better serve and protect consumers from Smart TV vulnerabilities.